2016
DOI: 10.1002/cmdc.201500515
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening and Experimental Validation Identify Novel Inhibitors of the Plasmodium falciparum Atg8–Atg3 Protein–Protein Interaction

Abstract: New therapies are needed against malaria, a parasitic infection caused by Plasmodium falciparum, as drug resistance emerges against the current treatment, artemisinin. We previously characterized the Atg8-Atg3 protein-protein interaction (PPI), which is essential for autophagy and parasite survival. Herein we illustrate the use of virtual library screening to selectively block the PPI in the parasite without inhibiting the homologous interaction in humans by targeting the A-loop of PfAtg8. This A-loop is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
(75 reference statements)
0
24
0
Order By: Relevance
“…Calculation of binding energies as a screening tool is highlighted by numerous implementations in medicinal chemistry and drug design [6][7][8]59]. Decomposing the binding energy into individual residue contributions can provide useful insight into the nature of the protein-ligand complex.…”
Section: Binding Energy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of binding energies as a screening tool is highlighted by numerous implementations in medicinal chemistry and drug design [6][7][8]59]. Decomposing the binding energy into individual residue contributions can provide useful insight into the nature of the protein-ligand complex.…”
Section: Binding Energy Analysismentioning
confidence: 99%
“…Structure-based drug design (SBDD) has benefited significantly over the years from developments in the field of proteomics, comparative genomics and high-end computing [1][2][3][4][5]. Binding affinity is an important metric in the assessment of new drug targets and their optimization [5][6][7][8]. The ability to calculate binding affinities reliably in silico is advantageous, reducing the need for expensive experiments [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Plasmodium, PfAtg8 -PfAtg3 interaction has been considered as an antimalarial drug target. Several small molecular inhibitors against Plasmodium in blood and liver stages have also been discovered (38,39). However, a recent study verified that three PfAtg8 -PfAtg3 interaction inhibitors identified in the Medicines for Malaria Venture Malaria Box do not block TgAtg8 lipidation, although all three inhibitors hinder Toxoplasma growth in a dose-dependent manner (40).…”
Section: Atg8 -Atg3 Interaction In Toxoplasma Gondiimentioning
confidence: 99%
“…Currently, targeting protein-protein interaction interfaces has been increasingly considered because of its importance and practicality (42)(43)(44). Recently, many compounds with antimalarial activity have been identified by inhibiting the recombinant PfAtg8 -PfAtg3 interaction in vitro, suggesting that the Atg8 -Atg3 interaction could be an attractive novel drug target in apicomplexan protozoans (28,38,39). In this study, we have developed a quantitative and straightforward AlphaScreen assay, which has enabled high-throughput screening of small-molecule modulators from compound libraries for multifarious biological targets.…”
Section: Atg8 -Atg3 Interaction In Toxoplasma Gondiimentioning
confidence: 99%
“…These differences were significant enough to result in an ϳ30-fold preference for the binding of small-molecule inhibitors for PfAtg8 compared to human LC3 (26). Moreover, high-throughput screens have identified numerous compounds that inhibit the interaction between recombinant P. falciparum Atg3 (PfAtg3) and PfAtg8 in vitro, including a group of compounds from the Medicines for Malaria Venture (MMV) Malaria Box with antimalarial activity in tissue culture (25)(26)(27). These findings illustrate the ability to specifically target the parasite Atg3-Atg8 interaction and suggest that the Atg3-Atg8 interaction may be an attractive new drug target in apicomplexan parasites.…”
mentioning
confidence: 99%